2017
DOI: 10.1177/2396987317698327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early cognitive-linguistic treatment for aphasia due to stroke: A randomised controlled trial (Rotterdam Aphasia Therapy Study-3)

Abstract: IntroductionOne third of patients with acute stroke have aphasia. The majority receive speech and language therapy. There is evidence for a beneficial effect of speech and language therapy on restoring communication, but it is unknown whether and how efficacy of speech and language therapy is influenced by timing of treatment. We studied whether speech and language therapy early after stroke by way of intensive cognitive-linguistic treatment is more effective than no speech and language therapy in the Rotterda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 27 publications
1
39
0
9
Order By: Relevance
“…One recent study has found no difference in language recovery between a group receiving intensive aphasia treatment compared to a group receiving no treatment. 50 In the context of the present study, it would be interesting to investigate how BDNF may interact with SLT in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has found no difference in language recovery between a group receiving intensive aphasia treatment compared to a group receiving no treatment. 50 In the context of the present study, it would be interesting to investigate how BDNF may interact with SLT in the chronic phase.…”
Section: Discussionmentioning
confidence: 99%
“…The largest and most robust of these is the Rotterdam Aphasia Therapy Study-3(RATS-3) [69], which enrolled 152 subjects in 14 centers across the Netherlands. RATS-3 enrolled patients within 14 days of a first stroke causing aphasia, randomized them to intensive speech therapy (ST), 1 h/day, 5 days/week for 4 weeks, or no therapy, and used the Amsterdam-Nijmegen Everyday Language Test (ANELT) at 4 weeks as the primary outcome.…”
Section: Human Trialsmentioning
confidence: 99%
“…For external validation of the SPEAK-model we used data from the Rotterdam Aphasia Therapy Study (RATS) – 3, a randomized controlled trial (RCT) studying the efficacy of early initiated intensive cognitive-linguistic treatment for aphasia due to stroke, conducted between 2012 and 2014 [ 21 , 22 ]. RATS-3 was approved by an independent medical ethical review board.…”
Section: Methodsmentioning
confidence: 99%
“…RATS-3 was approved by an independent medical ethical review board. Details about the study design, methods and results have been reported elsewhere and a summary will be provided below [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%